The Effect of Organizational Commitment and Job Satisfaction on Turnover Intentions - Dara Aulia Saragih; Hendy Hendy (Almana : Jurnal Manajemen dan Bisnis, 2022)
Employee turnover can create instability and uncertainty in the condition of employees, as well as an increase in recruitment costs. Therefore, a company is required to be able to retain its employees, such as being able to provide proper compensation and understand the things that can make its employees survive to keep working without reducing the overall performance of the company. This study intends to determine the effect of organizational commitment and job satisfaction on turnover intentions both independently and simultaneously. The research method used in this research is the descriptive quantitative method. The data analysis technique uses classical assumption test, and multiple linear regression analysis, while hypothesis testing uses partial test and simultaneous test. The results showed that organizational commitment and job satisfaction on turnover intentions. Simultaneously organizational commitment and job satisfaction on turnover intentions. The magnitude of the coefficient of determination of 0.67 means that the ability of the organizational commitment variable and job satisfaction to explain its influence on the turnover intention variable is 67%. While the remaining 33% is influenced by other independent variables not examined in this study such as work stress, conflict, compensation, and others. The conclusion states that partially and simultaneously, organizational commitment and job satisfaction affect turnover intentions.